Return statements : the return of religion in contemporary philosophy - Lambert, Gregg, 1961- (Incitements., 2016)
Gregg Lambert examines two facets of the return to religion in the 21st century: the resurgence of overtly religious themes in contemporary philosophy and the global ́⁰post-seculaŕ⁰₉ turn that has been taking place since 9/11. He asks how these two ́⁰₈returns to religioń⁰₉ can be taking place simultaneously, and explores the relationship between them. Lambert reflects on statements of these returns from contemporary philosophers including Alain Badiou, John D. Caputo, Jacques Derrida and Jean-Luc Nancy. He discovers a unique ́⁰₃ and forboding ́⁰₃ sense of the term ́⁰₈religioń⁰₉ that belongs exclusively to our contemporary perspective.